Profiling primaquine metabolites in primary human hepatocytes using UHPLC‐QTOF‐MS with 13C stable isotope labeling. (3rd February 2013) - Avula, Bharathi; Tekwani, Babu L.; Chaurasiya, Narayan D.; Nanayakkara, NP Dhammika; Wang, Yan‐Hong; Khan, Shabana I.; Adelli, Vijender R.; Sahu, Rajnish; Elsohly, Mahmoud A.; McChesney, James D.; Khan, Ikhlas A.; Walker, Larry A.
Abstract : Therapeutic efficiency and hemolytic toxicity of primaquine (PQ), the only drug available for radical cure of relapsing vivax malaria are believed to be mediated by its metabolites. However, identification of these metabolites has remained a major challenge apparently due to low quantities and their reactive nature. Drug candidates labeled with stable isotopes afford convenient tools for tracking drug‐derived metabolites in complex matrices by liquid chromatography‐tandem mass spectrometry (LC‐MS‐MS) and filtering for masses with twin peaks attributable to the label. This study was undertaken to identify metabolites of PQ from an in vitro incubation of a 1:1 w/w mixture of 13 C6 ‐PQ/PQ with primary human hepatocytes. Acquity ultra‐performance LC (UHPLC) was integrated with QTOF‐MS to combine the efficiency of separation with high sensitivity, selectivity of detection and accurate mass determination. UHPLC retention time, twin mass peaks with difference of 6 (originating from 13 C6 ‐PQ/PQ), and MS‐MS fragmentation pattern were used for phenotyping. Besides carboxy‐PQ (cPQ), formed by oxidative deamination of PQ to an aldehyde and subsequent oxidation, several other metabolites were identified: including PQ alcohol, predictably generated by oxidative deamination of PQ to an aldehyde and subsequent reduction, its acetate and the alcohol's glucuronide conjugate. Trace amounts of quinone‐imine metabolites of PQ and cPQ were also detected which may be generated by hydroxylation of the PQ/cPQ quinoline ring at the 5‐position and subsequent oxidation. These findings shed additional light on the human hepatic metabolism of PQ, and the method can be applied for identification of reactive PQ metabolites generated in vivo in preclinical and clinical studies. Copyright © 2013 John Wiley & Sons, Ltd.